Comparison of the parasite community of two notothens, Notothenia rossii and N. coriiceps (Pisces: Nototheniidae), from King George Island, Antarctica. Issue 6 (1st October 2018) - Muñoz, G.; Rebolledo, M.
Abstract: In this study, we analysed and compared the whole parasite community from the fish Notothenia rossii and Notothenia coriiceps collected from Fildes Bay at King George Island, Antarctica, during January–February 2017 in a field campaign supported by the Chilean Antarctic Institute. The fish samples collected were 45 specimens of N. rossii and 22 of N. coriiceps, with total lengths averaging 29.7 ± 5.3 cm and 32.5 ± 3.2 cm, respectively. Fish were dissected to collect their internal and external parasites. All the fish were parasitized; 13 taxa were found in N. rossii and 12 taxa in N. coriiceps . Acanthocephalans, mainly Metacanthocephalus johnstoni and Aspersentis megarhynchus, were the most abundant and prevalent parasites in both fish species. The abundance and richness of the parasite infracommunity increased with the host body length only in N. rossii . Twelve parasitic taxa were shared by both notothen species. Abundance and prevalence of parasitic taxa, as well as the average richness and abundance of the parasite infracommunities were mostly similar between the two fish species. Parasite compositions of N. coriiceps reported in published studies from King George Island were relatively comparable to our sample. We concluded that the two congeneric and sympatric fish species had highly similar parasite communities, which indicates that they use resources in a similar way, thus allowing them to become parasitized with the same parasitic species and in the same abundances. All parasites recorded in this study have been found in several other fish species; therefore, parasites from notothens are considered to be generalists.